Seed treatment with the fungicide fluopyram limits cotyledon infection by Leptosphaeria maculans and reduces blackleg of canola. Issue 4 (1st October 2020) - Peng, Gary; Liu, Xunjia; McLaren, Debra L.; McGregor, Linda; Yu, Fengqun
Abstract: Blackleg, caused by Leptosphaeria maculans, is a serious disease on canola or rapeseed in Canada, Australia and Europe. Disease levels have increased in western Canada recently and additional tools are needed to improve blackleg management. Seed treatment can be a cost-effective approach against blackleg, but there is currently no registered seed-treatment product targeting aboveground blackleg infection. In this study, a range of fungicides was evaluated for control of cotyledon infection by L. maculans and blackleg of canola. Under controlled environmental conditions, fluopyram showed greater efficacy than fluquinconazole (used against blackleg in Australia) in limiting cotyledon infection, while Prosper® EverGol and Helix® Vibrance (industry standards) were ineffective. Fluopyram at a rate of 30–150 g/100 kg seed generally inhibited cotyledon infection and this efficacy was not affected by delayed soil moisture for 3 weeks after planting. This indicates that the efficacy will unlikely be affected by a slight delay in germination due to a soil moisture deficit after seeding. In addition to typical mechanisms of succinate dehydrogenase inhibitor fungicides, fluopyram also induced expression of the indicator gene coding PR-1 proteins substantially, indicating the potential for inducing disease resistance. In field trials at 75 and 150 g/100 kg seed, fluopyram reduced the infection on cotyledons resulting from pricking inoculation on both susceptible and resistant canola cultivars, potentially limiting the infection into the stem. These seed treatment rates reduced the disease severity index (DSI) substantially on the susceptible cultivar, while DSI was low on a resistant cultivar with or without fluopyram treatment.